2022
DOI: 10.1161/strokeaha.121.037829
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Outcomes in Women: A Population-Based Cohort Study

Abstract: BACKGROUND: Limited data are available on sex-related disparities in long-term outcomes after stroke. We estimated sex differences in various stroke long-term outcomes among survivors after stroke in a prospective 25-year follow-up study. METHODS: Individuals recruited to the South London Stroke Register, an ongoing multi-ethnic urban-based population stroke register, from 1995 onward were included in the analyses (n=6687). The outcomes were death, subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 38 publications
5
32
0
Order By: Relevance
“…For instance, our findings suggest that female stroke survivors may represent an important sub-group who may be in greater need of support in the early discharge phase, given their poorer quality of life and greater severity depression and anxiety. This is consistent with previous studies which have found that female survivors have poorer outcomes than males even up to 5 years post-stroke [ 61 ]. Further research examining the effectiveness of strategies to improve psychosocial outcomes of stroke survivors is urgently needed, given few studies have demonstrated efficacy of such interventions.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, our findings suggest that female stroke survivors may represent an important sub-group who may be in greater need of support in the early discharge phase, given their poorer quality of life and greater severity depression and anxiety. This is consistent with previous studies which have found that female survivors have poorer outcomes than males even up to 5 years post-stroke [ 61 ]. Further research examining the effectiveness of strategies to improve psychosocial outcomes of stroke survivors is urgently needed, given few studies have demonstrated efficacy of such interventions.…”
Section: Discussionsupporting
confidence: 93%
“…124 Similarly, in a recent prospective 25-year follow-up study from the UK, women had a 9% lower risk of death than men after full adjustment, while they had a 30% higher risk of death than men in an unadjusted analysis. 4 In a pooled analysis of individual participant data from five acute stroke randomized controls trials, after multivariable adjustments, women with ischemic stroke had higher survival rates at 3-6 months than men; however, this higher survival rate in women was not significant for ICH. 125 Women have poorer functional recovery and lower quality of life (QOL) than men after stroke.…”
Section: Lifetime Endogenous Estrogen Exposurementioning
confidence: 99%
“…123 Stroke outcomes (Figure 3) Regarding stroke mortality, contradictory results have been shown depending on adjustments for confounders. 4,124 In the INSTRUCT (International Stroke Outcomes Study), a meta-analysis of individual participant data from 13 population-based incidence studies, the crude mortality rate ratio (MRR) was higher for women than men at 1 year (MRR [95% CI], 1.35 [1.24-1.47]) and 5 years (MRR [95% CI], 1.24 [1.12-1.38]). 124 However, these results were reversed after adjusting for confounders including age, pre-stroke functional limitations, stroke severity, and history of AF (1-year MRR [95% CI], 0.81 [0.72-0.92] and 5-year MRR [95% CI], 0.76 [0.65-0.89]); this indicates that women's higher mortality after stroke is attributable to these confounders (advanced age, greater stroke severity, worse pre-stroke status, and higher prevalence of AF).…”
Section: Lifetime Endogenous Estrogen Exposurementioning
confidence: 99%
See 2 more Smart Citations